Pandangan Gereja terhadap Budaya Kawin Adat Suku Biak Berdasarkan Ibrani 13:4 - Sinay, Steven Febri; Hutagalung, Stimson (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the Church's perspective on the traditional marriage customs of the Biak tribe based on Hebrews 13:4. The research uses a descriptive qualitative method to explore how the Church's religious values interact with the traditional marriage practices of the Biak tribe, focusing on the potential tensions and alignments between religious norms and cultural customs. The findings reveal that the Church's understanding of traditional marriage customs is crucial for creating harmony between religious teachings and local traditions. The Church plays a guiding role for its congregation to conduct marriages in accordance with religious teachings while still respecting existing cultural values. A wise approach from the Church can avoid conflicts and strengthen relationships between couples and the community by enriching the spiritual meaning of marriage through the integration of traditional cultural elements. This study also emphasizes the importance of a balanced understanding between faith and cultural traditions to build a strong foundation for marriages rooted in spiritual and cultural values. Furthermore, the Church acts as an agent of change, supporting spiritual and social growth within the Biak community, and fostering acceptance of cultural diversity in the context of marriage in the modern era